The establishment of muamalah court in Malaysia: an overview of issues and challenges - Hassan, Rusni; Hussain, Mohammad Azam (International Islamic University Malaysia, 2011)
ABSTRACT The blueprint for the establishment of SharÊÑah commercial court in judicial system that addresses legal issues related to Islamic banking and takaful has been included in the Financial Sector Master Plan 2001-2010. The judicial and legal department has taken proactive steps by establishing a special division under the civil court to deal with Islamic banking and financial matters based on the Arahan Amalan No. 1/2003 issued by Chief Justice, Dato’ Haidar Mohd Nor. Since 2003, muÑÉmalÉt cases have been registered in the High Court - Commercial Division 4. The specialized Muamalah Court began operation in February 2009 in High Court of Kuala Lumpur. This paper will trace the 1 LL.B(Hons), LL.M, PhD (IIUM), Associate Prof., AIKOL, International Islamic University Malaysia. 2 Lecturer, College of Law, Government & International Studies, Universiti Utara Malaysia, 06010 UUM, Sintok, Kedah Darul Aman. Currently, Ph.D candidate, Institute of Islamic Banking and Finance (IIBF), International Islamic University Malaysia. (2011) IIUMLJ SEd 119 120 IIUMLJ SPECIAL EDITION DEC 2011 origin, structure and function of the Muamalah Court and will seek to highlight the issues and challenges ahead. Keywords: Islamic financial system, Malaysia courts system, civil court, shari’ah court, muamalah court.